Anti‐Inflammatory Activities of Biapigenin Mediated by Actions on p38 MAPK Pathway. (19th August 2015) - Jnawali, Hum Nath; Park, Young‐Guen; Jeon, Dasom; Lee, Eunjung; Kim, Yangmee
<x xml:space="preserve">Abstract</x> <boxed-text content-type="graphic" id="bkcs10460-blkfxd-0001" position="anchor" orientation="portrait"> </boxed-text>